KARAKTERISTIK MATRIKS SOFT - Saman Abdurrahman; Thresye Thresye (LPPM Universitas Terbuka, 2020)
A soft set is a concept of the set that plays an essential role in overcoming vagueness. The soft set is an extension of the fuzzy set concept. One of the products of the soft set is a soft matrix. A soft matrix is a matrix formed into a soft set's membership value whose entries are elements at 0,1. This paper aims to introduce operations on soft matrices, i.e., intersection, union, and complements. Further, algebraic properties of soft matrix operations were investigated, commutative, associative, distributive laws, De Morgan’s laws, and absorption. Himpunan soft merupakan suatu konsep himpunan yang berperan penting dalam mengatasi ketidakpastian. Himpunan soft merupakan perluasan dari konsep himpunan fuzzy. Salah satu produk dari himpunan soft adalah matriks soft. Matriks soft adalah matriks yang dibentuk dari nilai keanggotaan himpunan soft yang entri-entrinya elemen di 0,1. Paper ini, bertujuan memperkenalkan operasi-operasi pada matriks soft, yaitu irisan, gabungan, dan komplemen. Lebih lanjut, diselidiki sifat-sifat aljabar operasi matriks soft, yaitu komutatif, asosiatif, hukum distributive, hukum De Morgan’s, dan absorpsi.